Strategi Berpikir Induktif sebagai Optimalisasi Statistik Pembelajaran di Era Digital Tingkat Sekolah Dasar - Balqis, Aulia Shinta; Khoirunnisya, Khofifah Afita; Audady, Moh. Syarukhan; Faturrohman, Mohammad Eka; Mahmudi, Kendid; Mahardika, I Ketut (Universitas PGRI Semarang, 2024)
Statistics plays a vital role in the process of collecting, analyzing, and interpreting data that underpins evidence-based decision-making. In the context of education in the digital era, it is imperative for teachers to apply an inductive thinking approach in teaching statistics, especially at the elementary school level. This approach not only facilitates students’ understanding of statistical concepts but also helps them develop critical thinking skills needed to face the challenges of the 21st century. This study discusses how inductive thinking strategies can be applied in statistics learning in elementary schools with the support of digital technology. The results show that the use of digital technology can make the learning process more interesting and interactive, and support important skills such as problem-solving, collaboration, and critical thinking. However, challenges such as low digital literacy among teachers and limited technological infrastructure in some areas remain. To overcome this, adequate training for teachers and increased investment in educational technology infrastructure are needed. In addition, changes to traditional learning methods need to be made so that this strategy can be implemented more effectively. Overall, this study confirms that with the right application of the approach, inductive thinking can improve the quality of statistics learning in the digital era and help prepare students with relevant skills for the future.